Training speed for the women's sprint hurdles - Thorson, M. (Track Coach, 2019)
It takes a very special blend of speed, speed endurance and strength and power to be a successful, elite women`s sprint hurdler. Many of the world`s best hurdle coaches have traditionally said that speed development is the most important ingredient in the women`s 100m hurdle race. Many coaches interpreted that to mean that there should be a primary focus on the pure speed component. Although speed is critically important, that is far from the case. Many leading hurdle coaches would actually place rhythm ahead of pure speed as the goal of their training programs. That will be addressed later. The great Jamaican coach, Stephen Francis, said an athlete who is looking to run 12.90 in the short hurdles should be capable of running 38 seconds in a 300-meter time trial. That is assuming, he said, the athlete can sprint 11.70-12.00 in the 100 meters. Francis went on to say that a hurdler with a goal of 12.3-12.4 should be able to negotiate a 300 in 36.0.